An American girl in the Hawaiian Islands : letters of Carrie Prudence Winter, 1890-1893 - Kofoid, Carrie Prudence, 1866-1942 (University of Hawaiʻi Press, 2012)
When twenty-three-year-old Carrie Prudence Winter caught her first glimpse of Honolulu from aboard the Zealandia in October 1890, she had "never seen anything so beautiful." She had been traveling for two months since leaving her family home in Connecticut and was at last only a few miles from her final destination, Kawaiaha'o Female Seminary, a flourishing boarding school for Hawaiian girls. As the daughter of staunch New England Congregationalists, Winter had dreamed of being a missionary teacher as a child and reasoned that "teaching for a few years among the Sandwich Islands seemed particularly attractive" while her fiancé pursued a science degree. During her three years at Kawaiaha'o, Winter wrote often and at length to her "beloved Charlie"; her lively and affectionate letters provide readers with not only an intimate look at nineteenth-century courtship, but many invaluable details about life in Hawai'i during the last years of the monarchy and a young woman's struggle to enter a career while adjusting to surroundings that were unlike anything she had ever experienced. In generous excerpts from dozens of letters, Winter describes teaching and living with her pupils, her relationships with fellow teachers, and her encounters with Hawaiian royalty (in particular Kawaiaha'o enjoyed the patronage of Queen Lili'uokalani, whose adopted daughter was enrolled as a pupil) and members of influential missionary families, as well as ordinary citizens. She discusses the serious health concerns (leprosy, smallpox, malaria) that irrevocably affected the lives of her students and took a keen (if somewhat naive) interest in relaying the political turmoil that ended in the annexation of the Hawaiian Islands by the U.S. in 1898. The book opens with a magazine article written by Winter and published while she was still teaching at Kawaiaha'o, which humorously recounts her journey from Connecticut to Hawai'i and her arrival at the seminary. The work is augmented by more than fifty photographs, four autobiographical student essays, and an appendix identifying all of Winter's students and others mentioned in the letters. A foreword by education historian C. Kalani Beyer provides a context for understanding the Euro-centric and assimilationist curriculum promoted by early schools for Hawaiians like Kawaiaha'o Female Seminary and later the Kamehameha Schools and Mid-Pacific Institute